2019
DOI: 10.1038/s41598-019-46935-w
|View full text |Cite
|
Sign up to set email alerts
|

Crystallized but not soluble uric acid elicits pro-inflammatory response in short-term whole blood cultures from healthy men

Abstract: Several epidemiological studies have pointed at serum uric acid (SUA) as an independent risk factor for mortality, diabetes, hypertension, cardiovascular and kidney disease; however, no clear pathogenic pathway is established. Uric acid (UA) crystals show pro-inflammatory properties and can thus create or contribute to the state of chronic low-grade inflammation, a widely accepted pathogenic mechanism in several of the above-mentioned pathologies. On the other hand, soluble uric acid possesses antioxidant prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 72 publications
(76 reference statements)
1
10
0
Order By: Relevance
“…1A) (17,18,20,22,37,38) and solubilizing UA with NaOH (Fig. 1B) (39,44). Checking the prepared solutions for contaminant crystals by light microscopy, we observed microcrystals even after sterile filtration of the UA solutions (5-50 mg/dl) upon prewarming UA but not upon solubilizing UA with NaOH (Fig.…”
Section: Sua Preparation Containing Microcrystals Elicits Opposite Effects In Monocytesmentioning
confidence: 90%
“…1A) (17,18,20,22,37,38) and solubilizing UA with NaOH (Fig. 1B) (39,44). Checking the prepared solutions for contaminant crystals by light microscopy, we observed microcrystals even after sterile filtration of the UA solutions (5-50 mg/dl) upon prewarming UA but not upon solubilizing UA with NaOH (Fig.…”
Section: Sua Preparation Containing Microcrystals Elicits Opposite Effects In Monocytesmentioning
confidence: 90%
“…Previous studies have shown the inflammatory program triggered by MSUc (18,50,51), and recently a work by Renaudin and colleagues (22) found that MSUc favored glycolytic activity of primed THP-1 cells. However, Renaudin´s work is limiting in identifying the mechanism involved in the MSUc effects in primary mouse and human macrophages.…”
Section: Discussionmentioning
confidence: 94%
“…Urate in its crystallin shape is phagocytized by monocytes or neutrophils causing the generation of pro-inflammatory cytokines such as IL-1. Furthermore, the internalization of UA crystals by leukocytes leads to production of free radicals, release of cathepsin B and activation of inflammasome (37,38). Interestingly, higher SUA levels have been hypothesized to play a protective role in the development of some neurological disorders such as dementia, multiple sclerosis, Alzheimer's disease and Parkinson's disease (39)(40)(41)(42).…”
Section: Uric Acid As Protective Factormentioning
confidence: 99%
“…Urate in its crystallin shape is phagocytized by monocytes or neutrophils causing the generation of pro-inflammatory cytokines such as IL-1. Furthermore, the internalization of UA crystals by leukocytes leads to production of free radicals, release of cathepsin B and activation of inflammasome ( 37 , 38 ).…”
Section: Uric Acid Metabolism and Biological Functions: A Brief Overviewmentioning
confidence: 99%